Results of aeromagnetic survey using unmanned aerial system at the Bunger Hills and Highjump Archipelago, Wilkes Land, East Antarctica - Aleksandr E. Simakov; Fedor G. Gutorov; German L. Leitchenkov; Aleksandr V. Golynskii; Vasilii G. Antsev; Dmitrii A. Golynskii (Записки Горного института, 2025)
The paper focuses on the technique and results of an aeromagnetic survey conducted using a fixed-wing unmanned aerial system (UAS) in East Antarctica at the Bunger Hills and Highjump Archipelago (Wilkes Land) during the 69th Russian Antarctic Expedition. The above survey was carried out at a 250-meter distance between flight lines (scale 1:25,000) over the area of 600 km2 to increase the geological knowledge of the area. The magnetic anomaly map obtained after data processing is more detailed than any of known published geological maps of the area. The size of anomalies detected varies from dozens of meters up to large, kilometer-scale structures traced within the entire area under survey. The data analysis shows that the surveyed region is characterized by morphological heterogeneity and amplitude variability of anomalous magnetic field. Along with relatively calm zones one can observe strong gradient ones. Even the fluent analysis of aeromagnetic survey results proves their high information content. The UAS-based survey results demonstrate that the technique implemented is an important tool of applied geophysics and can effectively solve tasks of geological mapping in harsh weather conditions of Antarctica. It can adequately replace conventional aeromagnetic surveys that are now done using manned aircraft.